EVALUATION OF CYTOTOXICITY OF THE AQUEOUS LEAF EXTRACT OF Pogostemon heyneanus Benth. (JAVA PATCHOULI) - Anjana Sheela; John Ernest Thoppil (SEAMEO BIOTROP, 2017)
Several plants have been recently reported to possess anticancer potential. Allium cepa root tip assay is a preliminary study to assess the cytotoxic effect of plant extracts. The cytotoxic activity of plants can be correlated to their anticancer potential. Cytotoxic potential of Pogostemon heyneanus (Lamiaceae) was evaluated using A. cepa root meristematic cells. This study was aimed at analyzing cytotoxic potential of P. heyneanus using Allium cepa root tip assay. Four different concentrations of the aqueous leaf extracts at three different durations were examined. Distilled water was used as control. The extract was found to be cytotoxic at all tested concentrations, when compared to control. Mitotic index was found to be decreasing with the increase in extract concentrations and treatment durations. The aqueous extract of P. heyneanus was found to be an effective cytotoxic agent, inducing various clastogenic and non-clastogenic aberrations such as chromosome gaps, bridges, multipolar anaphase, fragments, nuclear budding and lesions, hyperchromasia, laggards and mitotic pairing.